Synthesis, Characterization and Thermal Behaviour of Amino Functional Polymers from 4-Chloromethyl Styrene Polymers - Nasirtabrizi, M.H.; Ghashangi, Z.; Parchehbaf Jadid, A.; Nouri Molalar, M. (Asian Journal of Chemistry, 2012)
The 4-chloromethyl styrene was copolymerized with different styrenes monomers such as styrene, methyl styrene and 4-methoxy styrene by free radical polymerization at 70 ± 1 ºC using a,a'-azobis(isobutyronitrile) (AIBN) as an initiator and the copolymers I, II and III collected, respectively. The copolymer compositions were characterized by 1H NMR spectra and the polydispersity of the copolymers were determined using gel permeation chromatography. The phthalimide substituents were attached to the obtained copolymers with replacement of all the chlorine atoms in 4-chloromethyl styrene units. The hydrolysis of those polymers gave poly(4-aminomethyl styrene). The polymers, obtained in quantitative yields, were characterized by FTIR, 1H NMR spectroscopy and dynamic mechanical thermal analysis. All the polymers containing phthalimide groups and amino groups showed a high glass transition temperature (in the range 140-150 ºC) and (in the range 120-130 ºC), respectively in comparison with copolymers I-III (in the range 75-95 ºC).